Crystal structure of 2-methyl-N-[(4-methylpyridin-2-yl)carbamothioyl]-benzamide - Ameram, Nadiah; Adam, Farook; Fatihah, Nur Nadia; Al-Juaid, Salih (International Union of Crystallography, 2015)
In the title compound, C15H15N3OS, there is an intramolecular N—H O hydrogen bond and an intramolecular C—H S hydrogen bond involving the C O and C S bonds which lie on opposite sides of the molecule. The molecule is non-planar with the benzene and pyridine rings being inclined to one another by 26.86 (9). In the crystal, molecules are linked by pairs of N—H S hydrogen bonds, forming inversion dimers with an R2 2(8) ring motif. The dimers are linked via C—H S hydrogen bonds, forming slabs parallel to the bc plane.